Sensitivity of auditory perception to changes in phase spectrum - Štěpánková, Ivana (Lékař a technika, 2017)
This paper deals with sensitivity of human auditory to changes in sound phase spectrum. Although the human auditory system was considered “phase deaf” for a long time, nowadays a few recent studies proved that the change of sound phase spectrum has a significant impact on auditory perception. The aim of this paper is to verify these mentioned claims. To achieve this aim it is fundamental to perform listening tests with phase changed audio signals. The phase changes were applied to two groups of audio signals – synthetic signals and real signals. Thus, the listening test consisted of six different experiments and fourteen subjects participated in the listening test. The results of the test were statistically analyzed by ANOVA and the effect of phase changes to human auditory perception was determined based on these results.
Keywords: Research; výzkum; psychoakustika; Hearing Tests; lidé; Psychoacoustics; sluchové testy; Humans